Stepped Strabismus Surgery - Elkamshoushy A (Dove Medical Press, 2021)
Amr Elkamshoushy, Ahmed Kassem Department of Ophthalmology, Faculty of Medicine, University of Alexandria, Alexandria, EgyptCorrespondence: Amr ElkamshoushyDepartment of Ophthalmology, Faculty of Medicine, University of Alexandria, Alazarita, Alexandria, EgyptEmail elkamshoushy@gmail.comPurpose: To present stepped strabismus surgery as a novel technique in cases of small to moderate angle strabismus.Methods: Retrospective chart review of cases of stepped strabismus surgery from 2010 untill 2018. In stepped surgery, the first muscle is operated on under rapid induction-recovery IV propofol infusion. Patient is assessed in the OR. If deemed necessary, other muscles are operated on under general anesthesia. No adjustable sutures are used.Results: The technique was used in 22 cases of superior oblique palsy (SOP) (primary position hypertropia in the range of 12– 25 prism diopters) and 29 horizontal strabismus cases (angles in the range 12– 20 prism diopters). The first step was an inferior oblique myectomy in the SOP cases and a single rectus recession in the horizontal cases. After intraoperative assessment, 31% (16/51) needed additional muscle surgery. After 6 months of follow up, the overall reoperation rate was 9%. The technique was well tolerated by all patients.Conclusion: Stepped strabismus surgery is a useful technique for small to moderate angle strabismus cases with the potential for reducing the number of extraocular muscles operated on without compromising the surgical outcome.Keywords: anesthesia, anesthetics, intravenous, oculomotor muscles/surgery, propofol, retrospective studies, strabismus/surgery